Community Stigma Against COVID-19 Patients - Setiawan, Lilik; Suwardianto, Heru (Chakra Brahmanda Lentera Institute, 2021)
Background: Covid-19 is a contagious and dangerous disease. So that the sufferer must be isolated either independently at home, isolated in the hospital, or isolation in the village. In addition to patients, the community also implements health protocols. A person who is declared positive for Corona often gets negative prejudice, and gets unfavorable treatment, and is often shunned or ostracized by the community because people are afraid of being infected. This causes them to be labeled, stereotyped, discriminated against, and treated differently, and experience status harassment because they are associated with a disease. The purpose of the study was to find out community stigma about sufferers. Methods: The Design of this study was descriptive, with the research variable being community stigma about sufferers Covid-19. The population of the community research in Dusun Batu, Joho Village, Pace District, Nganjuk Regency, was 730 people and the sample was 73 respondents. The sampling technique used purposive sampling. The study was conducted on December 15-26, 2020. The research instrument was in the form of a questionnaire. The data were analyzed by percentage and interpreted to obtain quantitative data. Results: The results were obtained from 73 respondents, most of them 55 respondents (75%) with a negative stigma and a small proportion of respondents, namely 18 (25%) positive stigmatized respondents. The public's stigma about sufferers is Covid-19 influenced by several factors including age, education, occupation, whether or not they have received information about Covid-19, sources of information. Look for sources of information about Covid-19 that can be trusted Conclusion: By better understanding the information provided, it is hoped that the negative stigma will become positive about sufferers Covid-19. And from health workers to provide counseling to the community, so that people better understand the disease Covid-19 and maintain health protocols